The Selection - Cass, Kiera (Cass, Kiera. Selection novel, 2012)
"For thirty-five girls, the Selection is the chance of a lifetime. The opportunity to escape the life laid out for them since birth. To be swept up in a world of glittering gowns and priceless jewels. To live in a palace and compete for the heart of gorgeous Prince Maxon. But for America Singer, being Selected is a nightmare. It means turning her back on her secret love with Aspen, who is a caste below her. Leaving her home to enter a fierce competition for a crown she doesn't want. Living in a palace that is constantly threatened by violent rebel attacks. Then America meets Prince Maxon. Gradually, she starts to question all the plans she's made for herself -- and realizes that the life she's always dreamed of may not compare to a future she never imagined"--Provided by publisher.